Understanding technologically-induced customer services in the Nigerian banking sector: the internet as a post-modern phenomenon. (2016) - Ozuem, Wilson; Howell, Kerry E.; Lancaster, Geoff
Any discussion on technological adoption and use produces a diverse range views from both academics and practitioners. This has prompted some questions on its nature and understanding in developing countries like Nigeria. Assessing modernist and post-modernist perspectives through phenomenological hermeneutics and a capability-based model, this study examines the level of technologically induced customer services in the banking services sector on salient issues in sub-Saharan Africa. Drawing on a specific hermeneutical approach and the origins of modernist and post-modernist perspectives in developing societies, this paper examines this issue from a Nigerian perspective. A contemporary sub-Saharan e-business model is proposed. Results indicate that customer services in technologically-induced environments are increasingly becoming adopted in the context of financial services. As an embryonic mode of transaction, several variables are reported and some of these are hampering the development and adoption of this medium in Nigeria compared to those of developed countries.